Los otros beneficios de ser un papá comprometido - Kate Fogarty; Garret D. Evans (EDIS)
Having both parents involved in rearing their child has some obvious, and some maybe not-so-obvious, benefits for the child, the family, and for fathers themselves. This 5-page fact sheet was written by Kate Fogarty and Garret D. Evans and published by the UF Department of Family Youth and Community Sciences, May 2011.